2016
DOI: 10.1007/s13770-016-9114-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactor conditioning of valve scaffolds seeded internally with adult stem cells

Abstract: The goal of this study was to test the hypothesis that stem cells, as a response to valve-specific extracellular matrix “niches” and mechanical stimuli, would differentiate into valvular interstitial cells (VICs). Porcine aortic root scaffolds were prepared by decellularization. After verifying that roots exhibited adequate hemodynamics in vitro, we seeded human adipose-derived stem cells (hADSCs) within the interstitium of the cusps and subjected the valves to in vitro pulsatile bioreactor testing in pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Multiple cell types have been proposed as VIC precursors including ECs, myofibroblasts, and several stem cell types (Schenke-Layland et al, 2003;Sutherland et al, 2005;Dohmen et al, 2006;Schmidt et al, 2010;Harrington et al, 2011;Kennamer et al, 2016). Here, we show that in uninjured valves a small number of cells derived from ECs, the main source of VICs in amniotes (Snarr et al, 2008;Jain et al, 2011;Wessels et al, 2012;MacGrogan et al, 2014;Liu et al, 2018), express nfatc1, suggesting that some ECs undergo EndoMT and contribute to the replacement and maintenance of VICs in homeostatic conditions.…”
Section: Multi-cellular Contribution To Cardiac Valve Regenerationsupporting
confidence: 49%
“…Multiple cell types have been proposed as VIC precursors including ECs, myofibroblasts, and several stem cell types (Schenke-Layland et al, 2003;Sutherland et al, 2005;Dohmen et al, 2006;Schmidt et al, 2010;Harrington et al, 2011;Kennamer et al, 2016). Here, we show that in uninjured valves a small number of cells derived from ECs, the main source of VICs in amniotes (Snarr et al, 2008;Jain et al, 2011;Wessels et al, 2012;MacGrogan et al, 2014;Liu et al, 2018), express nfatc1, suggesting that some ECs undergo EndoMT and contribute to the replacement and maintenance of VICs in homeostatic conditions.…”
Section: Multi-cellular Contribution To Cardiac Valve Regenerationsupporting
confidence: 49%
“…Despite this work is not the first to employ a bioreactor system to assess cell viability inside a decellularized scaffold for cardiac valve engineering (33,34), it is the first to address the problem of valve maturation of a fully recellularized tissue using a systematic proteomic approach. In fact, our mass spectrometry data clearly showed that compared to the native pericardial membrane, a number of proteins were upregulated in the material as a result of de-novo protein synthesis by the introduced valve cells.…”
Section: Discussionmentioning
confidence: 99%
“…We are now planning new studies with human-derived bone marrow/adipose-derived mesenchymal stem cells and scaled up bioreactors able to efficiently repopulate decellularized pericardial patches with surgical size. It will be also interesting to assess whether mounting the recellularized pericardial material onto stent posts and valve pulse duplicators will promote further biological maturation of the living pericardium material due to mechanical conditioning (41), and will maintain the viability of the cells under tissue mechanical stress (33), as a step forward in translation of the living pericardium material for clinical employment.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical heart valves require patients to be on life-long anticoagulant medication; bioprosthetic valves are less durable and more prone to re-calcification. Scientists and engineers have been exploring alternative treatments such as tissue engineered heart valves using bioreactor systems to deliver the proper flow, flex, and stretch conditioning (116,117).…”
Section: Our Laboratory's Experience In Valve Regenerative Medicinementioning
confidence: 99%